Lignans are the main active components of Schisandrae Chinensis Fructus for liver disease treatment: a review - Ke Fu; Shu Dai; Cheng Ma; Yafang Zhang; Shenglin Zhang; Cheng Wang; Lihong Gong; Honglin Zhou; Yunxia Li (Food Science and Human Wellness)
As a traditional Chinese herbal medicine, Schisandrae Chinensis Fructus (SC) has been used in medicine and food industry due to its health care and therapeutic effects. Over the past 20 years, the use of SC and its active ingredient lignans in the prevention and treatment of liver diseases has been increasing, and their hepatoprotective effects has increased the interest of the public and academia. Therefore, in the present work, we first determined the effectiveness of SC in the treatment of liver diseases such as metabolic associated fatty liver disease, alcoholic liver disease, cholestatic liver disease and acute liver injury. Subsequently, the pharmacological effects and molecular mechanisms of lignans, the active components of SC, for liver disease treatment were comprehensively summarized for the first time. The results showed that the lignans in SC could achieve hepatoprotective effects by regulating lipid metabolism, anti-fibrosis, anti-inflammation, anti-oxidation, anti-tumor and regulating bile acid metabolism. The mechanism mainly involved adenosine 5’-monophosphate-activated protein kinase, endoplasmic reticulum stress, sterol regulatory element binding protein 1c, autophagy, transforming growth factor-β, mitogen-activated protein kinase, microRNA, nuclear factor kappa-B, nuclear factor erythroid-2-related factor 2, heat shock proteins and pregnane X receptor signaling pathways. These results can lay a scientific foundation for the development of hepatoprotective drugs or functional foods from SC/lignans.